Neovochthonius nom. nov. pro Neochthonius Karppinen (Acari, Oribatei, Protoplophoroidea, Heterochthoniidae) - Judson, Mark L. I. (Zootaxa, 2009)
The oribatid genus Neochthonius Karppinen in Golosova & Karppinen, 1984 was erected for a single species of Heterochthoniidae, Neochthonius latisetosus Golosova & Karppinen, 1984, from Sakhalin Island, Russian Far East (Golosova & Karppinen 1984). As noted by Judson (1995), this name is preoccupied by the pseudoscorpion genus Neochthonius Chamberlin, 1929. Although sometimes treated as a synonym of Kewochthonius Chamberlin, 1929 [now a junior synonym of Chthonius C. L. Koch, 1843] in the past, Neochthonius Chamberlin is currently considered to be a valid genus, containing four species from California, U.S.A. (Judson 1990; Muchmore 1996). Despite repeated letters to Dr Karppinen (the first sent in 1991), advising him that Neochthonius Karppinen was preoccupied, no replacement name has been published and I am informed that he has now given up all zoological activity (R. Penttinen, in litt.). In order to remove this homonymy, Neochthonius Karppinen, 1984 is here replaced with Neovochthonius nom. nov. (etymology: Latin prefix ne-, meaning ‘not’, added to the name of the related genus Ovochthonius; gender masculine). Neochthonius latisetosus Golosova & Karppinen, 1984 therefore becomes Neovochthonius latisetosus (Golosova & Karppinen, 1984) comb. nov. No other species have been assigned to this genus.